Two new species of the syringophilid quill mites (Acari: Prostigmata: Syringophilidae) parasitizing apodiform birds (Aves: Apodiformes) - Skoracki, Maciej; Kaszewska, Katarzyna; Kavetska, Katarzyna (Zootaxa, 2015)
Two new syringophilid species (Acariformes: Syringophilidae) are described, Apodisyringiana hirundapi sp. nov. from Hirundapus caudacutus (Latham) from Japan and Syringophiloidus apus sp. nov. from Apus melba (Linnaeus) from Chile.